Performance Improvement of Cold Rolling Mill to Contribute more for The Profitability of PT Krakatau Steel - Wirawan, Wahyu; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2013)
Management is currently facing a difficult dilemma because of the three products that generate revenue for the company only one that gives a good profitability. Cold Rolled Coil (CRC) is one of the products that currently contribute less profit for the company even tend to contribute loss. Management is always worried if the volume of CRC is increased will further increase losses, but if the volume is too small then the cost of production will rise due to the high fixed costs. On the other hand, Hot Rolled Pickled and Oiled (HRPO) which is also the output of Cold Rolling Mill (CRM) always give a positive contribution and need to be increase its production volume and sales. This increase in volume of HRPO will of course affect to how much of CRC can be produced due to the space of Continuous Pickling Line (CPL), the first line of CRM, Â will be occupied to produce HRPO. Performance improvement is needed to get the best margin by increasing the sales volume of HRPO while CRC is not being sacrified. Â Keywords: Performance Improvement, Profitability, Efficiency, Effectiveness, Hot Rolled Pickled and Oiled (HRPO), Cold Rolled Coil (CRC), Cold Rolling Mill (CRM).